2015
DOI: 10.2320/matertrans.ma201538
|View full text |Cite
|
Sign up to set email alerts
|

Pt- and Ag-Decorated Carbon Nanotube Network Layers for Enhanced NH<sub>3</sub> Gas Sensitivity at Room Temperature

Abstract: Multi-walled carbon nanotubes (CNTs) were directly grown on alumina substrates patterned with Pt interdigitated electrodes by chemical vapor deposition method to fabricate gas sensor. Pt and Ag thin layers with nominal thicknesses of 2 and 4 nm were coated on the CNT layer by evaporation method to modify the CNT properties. The gas sensing results showed that the CNT/Pt-and CNT/Ag-based sensors exhibited enhanced sensitivity to NH 3 gas at room temperature. The responses of the CNT/Pt (3.0%) and CNT/Ag (6.9%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…The WO 3 /MWCNT composite-based sensors showed not only an improvement of the sensor responses but also a decrease of their response time and recovery time. As showed in the previous study [10], the gas-sensing mechanism of the CNT-based sensor coated with noble metallic nanoparticles is due to the Schottky barrier height between the metal nanoparticles and MWCNTs. Meanwhile the gas sensing property of WO 3 nanostructures is explained by the presence of oxygen molecules adsorbed on the WO 3 nanoparticles surface in their ionic form of O 2…”
Section: Resultssupporting
confidence: 54%
“…The WO 3 /MWCNT composite-based sensors showed not only an improvement of the sensor responses but also a decrease of their response time and recovery time. As showed in the previous study [10], the gas-sensing mechanism of the CNT-based sensor coated with noble metallic nanoparticles is due to the Schottky barrier height between the metal nanoparticles and MWCNTs. Meanwhile the gas sensing property of WO 3 nanostructures is explained by the presence of oxygen molecules adsorbed on the WO 3 nanoparticles surface in their ionic form of O 2…”
Section: Resultssupporting
confidence: 54%
“…The detail of the gas-sensing measuring system could be found elsewhere. [8,[33][34][35] 3. RESULTS AND DISCUSSION…”
Section: Fabrication and Characterization Of Gas Sensormentioning
confidence: 99%
“…The results showed that the response was linearly proportional to the NH3 concentrations with the sensitivity (or the slope of the linear line) was 0.0081 times/ppm. From linear relationship between response and NH3 gas concentration, the detection limit (DL) of the sensor was calculated via following equation [8,[33][34][35] DL = 3 × (rms/slope) (1) where rms is the root-mean-square deviation extrapolated from the fifth-order polynomial fit of the baseline (figure 6c); the slope is the sensitivity of gas sensor, which was extracted from the linear fit of response versus the NH3 concentration (figure 6b). The calculated DL was 0.32 ppm which implied a high potential of PS-LFO for the sub-ppm NH3 gas detection.…”
Section: Gas-response Characteristics Of Materialsmentioning
confidence: 99%